1976
DOI: 10.1071/bi9760513
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Cystine by Merino Sheep Genetically Different in Wool Production IV. Rates of Entry of Cystine Into Plasma, Measured With a Single Intravenous Injection of L- [35S] Cystine, and the Subsequent Incorporation of 35S Into Wool Fibres

Abstract: Ten, 2-year-old Merino ewes from a flock selectively bred for high clean fleece weight (Fleece Plus) and ten from a flock bred for low clean fleece weight (Fleece Minus) were randomly divided between two dietary treatments: 600 or 1100 g/day of pelleted lucerne hay. After 14 weeks, each ewe received an intravenous injection of . Venous blood samples were collected at 15 specified times until 8 h after the injections, and wool fibres were plucked until 65-75 days after the injections.Protein-free filtrates prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The measurements of cyst(e)ine ILR in the present study were 15-38 mmol/day (1-8-4-6 g/day); values which are somewhat higher than previously reported ILR values in sheep (Williams et at. (1972) 14 mmol/day; Williams (1976) 14-21 mmol/day; Pisulewski & Buttery (1985) 10 mmol/day; Fenn & Leng (1989) 12 mmol/day). Some of these differences may be related to the age and dietary intake of the animals studied.…”
Section: Whole Body Thiol Fluxmentioning
confidence: 98%
See 1 more Smart Citation
“…The measurements of cyst(e)ine ILR in the present study were 15-38 mmol/day (1-8-4-6 g/day); values which are somewhat higher than previously reported ILR values in sheep (Williams et at. (1972) 14 mmol/day; Williams (1976) 14-21 mmol/day; Pisulewski & Buttery (1985) 10 mmol/day; Fenn & Leng (1989) 12 mmol/day). Some of these differences may be related to the age and dietary intake of the animals studied.…”
Section: Whole Body Thiol Fluxmentioning
confidence: 98%
“…The sheep in Expl 2 were lambs and showed higher cysteine ILRs (30-38 mmol/day) than the mature sheep used in Expt 3 (15 mmol/day) and other studies. The supplementation study of Fenn & Leng (1989) fed mature sheep a basal diet of only 800 g of oaten chaff a day and so it is perhaps not surprising that their basal ILR values were low as Williams et al (1972) and Williams (1976) demonstrated that cysteine ILR is significantly depressed with lowered intake. Williams (1976) also suggests that continuous infusion may underestimate ILR compared with a single injection approach because of the extent of [ 35 S]-recycling between free and disulphide-bound cysteine.…”
Section: Whole Body Thiol Fluxmentioning
confidence: 99%
“…Similarly, systemic hormonal differences between genetically-different sheep are small and inconsistent (Williams et al 1986;Hynd 1988;Williams et al 1990), as are differences in the level of various metabolites, with the exception of cysteine (Williams et al 1972;Williams 1976). Difference in plasma cysteine levels between genotypes are probably a reflection of a differential ability of the follicles to extract and utilise the amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine is vital for wool growth and is usually the first limiting amino acid for wool fibre synthesis [171]. Sheep selected for high wool production tend to have lower blood cysteine and GSH concentrations than those selected for low wool production [128,290]. Low concentrations of GSH can be associated with impaired animal health as cysteine and GSH play a key role in the regulation of the immune response [79].…”
Section: Antioxidantsmentioning
confidence: 99%